Determination of icewine lipids by Ultra High Performance Liquid Tandem Chromatography Quadrupole Time-of-Flight Mass Spectrometry - YANG, Jing; JIANG, Kuaile; QU, Peng; WAN, Sibo; HU, Qixiu; MAO, Ruzhi (Food Science and Technology, 2023)
Backgroud: Icewine is a unique food in the world. Lipids in icewine are nutritious and healthy for humans. However, limited studies are available on the qualitative and quantitative analysis of icewine. Method: UPLC-QTOF-MS approach to study lipids in icewine. Bioinformatics strategies will expand the applications of lipidomics in food science,OPLS-DA) was performed to visualise group separation and recognized significantly transform metabolites. Results: In the present study, lipid molecules belonging to 5 classes were qualitatively and quantitatively analysed. The lipids studied were as track: 102 triacylglycerols (TAG), 18 free fatty acids (FFA), 5 diacylglycerols (DAG), 6 ceramides and sphingosine-1-phosphate (Cer), and 1 N-palmitoyl-D-erythro-sphingosylphosphorylcholine (SM). The Shangri-La icewine has higher TAG and FFA content than the Canadian icewine. However, in Canadian icewine samples, the DAG (16:0/16:1) content (398.26 μg/mL) was higher than that of Shangri-La icewine specimens (522.43 μg/mL). The SM (14:0) content in Canadian icewine was higher than that of Shangri-La icewine. Conclusion:UPLC-QTOF-MS is an effective method for detecting lipids in icewine samples. The primary fundamental lipids in icewine samples were TAG, FFA, DAG, Cer, and SM. Therefore, Shangri-La icewine is more nutritious for human health than Canadian icewine.